Sistema de contabilidad gubernamental y toma de decisiones en la Unidad Ejecutora de Salud Ucayali Contamana año 2022 - Torres Sangama, Milagros (2022)
The research determined as an objective to determine the relationship between the government accounting system and decision making in the Ucayali Contamana Health Execution Unit in 2022. Opting as an applied type study, descriptive level - correlational, experimental design. The research was used as a technique to the survey and the questionnaire as an instrument to collect information. Concluding that the government accounting system is handled on a regular basis (24%) since the information recorded by the staff is almost never automatically synchronized; Likewise, the accounting information in order to the concurrence of the economic facts is almost never presented, since the accounting record guarantees transparency in the execution of the resources, they never consider it. For its part, decision-making has been carried out regularly (22%), due to the lack of integrity, it is sometimes the main problem in the institution, and the accounting record system is never a good management tool, but having a greater number of possible alternatives always helps to solve problems. Likewise, it was determined that there is a significant relationship between the Government Accounting System and decision making, corroborated by a correlation coefficient of 0.580 at a medium positive level, and a (bilateral) significance of 0.000.